PENGARUH HARGA DAN DESAIN TERHADAP MINAT PEMBELIAN DIfDISTRO OVERTOUN MALANG - Muhammad Syaiful Rojikin; Muhammad Mansur (UNIVERSITAS ISLAM MALANG, 2018)
DABSTRACTW MarketingHmanagementKisAtheAartKandLscienceKofLchoosingKtheLtargetmarketKandPreachingOforOmaintainingPandKgrowingLcustomersPbyPcreating. This studyHaimsKtoGdetermineKhowKmuchLinfluence the harha and design have on consumers' interest in being Overtoun Distro Malang. The results of this study indicate that prices and designs can be said to be good. Pricesand designs have an effect of 21% on buying interest Keywords: Price, Design, Purchase Interest